Inhibition of Integrin-Mediated Platelet Aggregation, Fibrinogen-Binding, and Interactions with Extracellular Matrix by Nonpeptidic Mimetics of Arg-Gly-Asp - Varon, David; Lider, Ofer; Dardik, Rima; Shenkman, Boris; Alon, Ronen; Hershkoviz, Rami; Kapustina, Galina; Savion, Naftali; Martinowitz, Uri; Greenspoon, Noam (Thrombosis and Haemostasis, 1993)
The interaction of the activated platelet integrin, glycoprotein IIb-IIIa (GPIIb-IIIa) with fibrinogen and von-Wille-brand factor (vWF) is essential for platelet aggregation. The minimal structure required for this integrin’s binding to fibrinogen is the Arg-Gly-Asp (RGD) sequence. Inasmuch as normal level of GPIIb-IIIa-RGD interactions are required for maintaining hemostasis, elevated platelet aggregation can cause adverse pathological effects. We have previously reported that nonpeptidic mimetics of RGD, consisting of carboxylate and guanidinium groups of Asp and Arg divided by a linear 11-atom spacer, acquired a significant affinity for the GPIIb-IIIa integrin and inhibited platelet aggregation. The structural requirements for the interactions of the RGD sequence with GPIIb-IIIa and the inhibitory potential of a newly designed series of mimetics on platelet aggregation and interactions with extracellular matrix (ECM) were assayed herein. Adenosine-diphosphate (ADP)-induced platelet aggregation was inhibited in a dose-dependent manner by various RGD mimetics, with a maximal inhibition of 80-100% with an IC50 of 3 μM for the most potent inhibitor, NS-11 which a six-membered ring was introduced into the spacer chain, which exceeded the IC50 attained with the original RGDS peptide. The inhibitory effect of the RGD mimetics was attributed to their specific interaction with the GPIIb-IIIa integrin, since these mimetics inhibited the binding of the PAC-1 mAb to GPIIb-IIIA. Furthermore, the binding of 125I-labeled fibrinogen to platelets was inhibited by the RGD surrogates in a dose-dependent and saturable manner. The RGD-mimetics also inhibited up to 70% the adhesion, aggregation, and deposition of platelets onto ECM. Thus, we suggest that the novel nonpeptidic mimetics of RGD described herein, which were shown to be resistant to proteolytic digestion, would be valuable in novel therapeutic approaches to treat in RGD-dependent pathological disorders involving platelet-ECM interactions.